1997
DOI: 10.1007/bf02592238
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric measurement of human calf muscle from magnetic resonance imaging

Abstract: Muscle mass is a determining factor in skeletal muscle function and is affected by inactivity, immobilization, disease, and aging. The aim of this study was to develop an objective and time-efficient method to quantify the volume and cross-sectional area of human calf muscles using three-dimensional magnetic resonance images. We have estimated the errors incurred in muscle volume measurements arising from artifacts known to occur in magnetic resonance imaging (MRI). The largest source of error was due to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 17 publications
0
37
0
1
Order By: Relevance
“…The fat-free max-CSA was determined pre-and post-RPT using a custom-designed interactive computer program that allows for correction of partial volume filling effects, as described previously. 11,12 In addition, we previously showed that the max-CSA of individual PF muscles can be measured reliably, with test-retest correlation coefficients of 0.978-0.999.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 96%
“…The fat-free max-CSA was determined pre-and post-RPT using a custom-designed interactive computer program that allows for correction of partial volume filling effects, as described previously. 11,12 In addition, we previously showed that the max-CSA of individual PF muscles can be measured reliably, with test-retest correlation coefficients of 0.978-0.999.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 96%
“…Chemically selective fat suppression was used to enhance the deWnition between muscle groups. The fatfree maximal muscle cross-sectional area (max-CSA) of the posterior compartment muscles was determined using a custom-designed interactive computer program that allows for correction of partial volume Wlling eVects, as described previously (Elliott et al 1997). Posterior compartment muscles included in the analysis were the medial gastrocnemius, lateral gastrocnemius, and soleus muscles, which serve as important plantarXexors of the ankle.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Image analysis was performed using a custom-designed interactive computer program, EXTRACTOR. 17 Treadmill and cycling locomotor training In both types of training, animals were trained continuously for 3 months (5 days per week, two sessions per day, 20 min per session), starting on postoperative day 8.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%